Physical and Emotional Health Information Needs and Preferences of Long-Term Prostate Cancer Survivors - Zhou, Eric S. (Patient Educ Couns, 2016)
OBJECTIVE: Many men diagnosed with prostate cancer (PC) will experience physical and psychosocial late effects of treatment. Their interest/preferences for receiving information about addressing common sequelae is not well understood. We examined long-term PC survivors’ level of interest, whether this differed based upon symptomatology, and their preferred coping information source. METHODS: N=615 PC survivors (3–8 years post-diagnosis) completed a survey on physical and psychological health and their information interests and preferences related to late effects of cancer treatment. RESULTS: Over half of PC survivors reported interest in information about late effects of treatment or sexual health, while approximately a quarter were interested in emotional health information. Survivors preferred to receive information about late effects of treatment from their oncologists, sexual health information from their primary care providers (PCP), oncologist, or written/online resources, and emotional health information from their PCP. Information needs were more commonly reported among men with poorer domain-specific health functioning. CONCLUSION: Long-term PC survivors report significant interest in receiving information about their physical, sexual, and emotional health. PRACTICE IMPLICATIONS: Medical providers caring for these men should inquire about survivors’ information needs and future intervention efforts should consider who delivers the information, dependent upon the type of dysfunction reported.